1985
DOI: 10.1139/e85-005
|View full text |Cite
|
Sign up to set email alerts
|

Petrology of the Grenville swarm of gabbro dikes, Canadian Precambrian Shield

Abstract: The Grenville tholeiitic dikes of Late Proterozoic or early Paleozoic age cut marbles and gneisses of the Grenville Province within and adjacent to the Ottawa rift structure. Where traversed the swarm consists of about 40 large dikes (up to 100 m wide) representing a crustal extension of 1 km. The principal minerals are olivine, augite, pigeonite, plagioclase, magnetite, ilmenite, K-feldspar, and quartz. Crystals of pigeonite around olivine and complex augite–pigeonite composite grains suggest that the reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Thinner dykes are known, some only a few cm thick but always occur in the vicinity of thicker parent dykes, so are just offshoots or apophyses. To the east dykes are more numerous with a greater range in thickness (from 3 to 100 m with a mean of 30 m from 7 dykes, Kretz et al, 1985), which may support the idea that thicker master dykes travel farther from the plume source than thin ones, leading to a skewed distribution towards thicker dykes with increasing distance travelled.…”
Section: Geological and Geophysical Backgroundmentioning
confidence: 66%
See 2 more Smart Citations
“…Thinner dykes are known, some only a few cm thick but always occur in the vicinity of thicker parent dykes, so are just offshoots or apophyses. To the east dykes are more numerous with a greater range in thickness (from 3 to 100 m with a mean of 30 m from 7 dykes, Kretz et al, 1985), which may support the idea that thicker master dykes travel farther from the plume source than thin ones, leading to a skewed distribution towards thicker dykes with increasing distance travelled.…”
Section: Geological and Geophysical Backgroundmentioning
confidence: 66%
“…We do not know if this pattern exists along the entire length of the Grenville swarm; both high and low TiO 2 diabase dykes are known in more easterly locations (e.g. Kretz et al, 1985;Kumarapeli et al, 1990;Seymour and Kumarapeli, 1995) but a central concentration of the former cannot be tested from the information available.…”
Section: Geochronologymentioning
confidence: 97%
See 1 more Smart Citation
“…%) of element oxide or parts (1983) expressed precision in terms of k, defined as Introduction Gabbroic rocks are widespread in the southern Grenville Province of the Canadian Shield and have recently attracted much attention. Their distribution was shown in a compilation by Baer et al (1977), and detailed studies have been carried out by Buddington (1939), Whitney and McLelland (1973), Grieve and Gittins (1975), Nadeau (1984), Kretz et al (1985, Davidson and Grant (1986), Grant (1988), and others. The present study deals with certain metamorphosed gabbroic and associated ultramafic rocks (metagabbro complexes) that lie northwest of Ottawa ( Fig.…”
mentioning
confidence: 91%
“…In a previous study of the Grenville swarm of gabbro dikes (Kretz et al 1985), data were reported on the microstructure of the gabbro, especially on the shape, size, and spatial distribution of crystals of olivine, calcic pyroxene, pigeonite, and plagioclase. The focus at present is on the shape of Ti-bearing magnetite, especially on crystals found in a relatively narrow (2 m wide) dike.…”
Section: Introductionmentioning
confidence: 99%